Reconstructing Digital Tax Oversight of Content Creators in Indonesia - Qonitah Zalfa Primayudhana; Ismiyanto Ismiyanto; Hanuring Ayu Ardhani Putri (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The rapid expansion of the digital economy has significantly increased the number of content creators as taxpayers while simultaneously accelerating the Directorate General of Taxes’ (DGT) adoption of digital technologies to monitor tax compliance. One such mechanism involves the use of publicly accessible social media content, which continues to raise concerns regarding legal certainty and the limits of governmental authority. This study aims to analyze the legal framework governing the tax reporting obligations of content creators and to examine the legal ambiguity surrounding the DGT’s authority to use social media content as the basis for issuing a Tax Data Clarification Request (SP2DK) and initiating tax audits. This research employs a normative legal methodology using statutory, conceptual, comparative, and cyber law approaches. The findings indicate that Indonesia’s tax legal framework recognizes income earned by content creators as taxable income. However, Article 35A of the Law on General Provisions and Tax Procedures (KUP Law) does not explicitly authorize the use of social media content as a source of tax supervisory data, resulting in regulatory uncertainty and inconsistent legal interpretation. This study concludes that harmonization of the KUP Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law is necessary to establish a comprehensive legal framework that upholds the principles of legality, proportionality, accountability, legal certainty, and the protection of taxpayers’ constitutional rights within the digital tax administration system.